Pathways towards people-oriented conservation in a human-dominated landscape: the network for conserving Central India. Issue 1 (1st January 2021) - Neelakantan, Amrita; Rithe, Kishor; Tabor, Gary; DeFries, Ruth
ABSTRACT: Landscape-level conservation that maintains biodiversity and livelihoods for local people requires long-term collaborations across local communities, scientists, practitioners and decision-makers. The Network for Conserving Central India (NCCI) provides a platform for such collaborations in a globally important tiger conservation region within a complex social-ecological system. Using the NCCI as an example, our study identifies indicators to track progress in collaborative landscape-level networks across four dimensions: the composition of the network; collaborative scientific output; dissemination of research outputs through social, electronic and print media; and participation in policy and decision-making bodies. The NCCI is primarily comprised of members of the scientific community, Non-Governmental Organizations (NGOs) and various levels of government. Since 2013, the NCCI members conducted research that predominantly addressed human-wildlife conflicts and human livelihood needs around protected areas (PAs), with less attention to forest ecology and climate. NGOs within the NCCI work closely with local communities and provide avenues for local engagement. Co-production of policies is an essential but challenging goal due to established hierarchies and top-down institutional structures. Our analyses highlight the NCCI's role as a knowledge platform and bridge among researchers, NGOs, and government, with significant opportunities for boundary work in the Science, Policy and Practice Interface (SPPI). A challenging and unfulfilled goal is the engagement of local communities to co-produce approaches that balance conservation, local livelihoods, and development. We suggest that other landscape-level networks in social-ecological systems can modify these dimensions as pertinent to their respective circumstances to track progress towards co-produced management to address livelihood and conservation needs.